Regulation of IL-22BP in psoriasis - Voglis, Stefanos; Pezer, Silvia; Schäkel, Knut; Kurschus, Florian (Scientific reports, 2018)
IL-22 is a potent pro-inflammatory cytokine upregulated in psoriasis and in other inflammatory diseases. The function of IL-22 is regulated by the soluble scavenging receptor, IL-22 binding protein (IL-22BP or IL-22RA2). However, the role and regulation of IL-22BP itself in the pathogenesis of inflammatory disease remain unclear. We used the TLR7 agonist Imiquimod (IMQ) to induce a psoriasis-like skin disease in mice and found a strong downregulation of IL-22BP in the affected skin as well as in the lymph nodes of animals treated with IMQ. We also analysed psoriatic skin of patients and compared this to skin of healthy donors. Interestingly, IL-22BP expression was similarly downregulated in skin biopsies of psoriasis patients compared to the skin of healthy donors. Since IL-22BP is expressed foremost in dendritic cells, we characterized its expression in monocyte-derived dendritic cells (MoDC) during maturation. In this way, we found Prostaglandin E2 (PGE2) to be a potent suppressor of IL-22BP expression in vitro. We conclude that regulation of IL-22BP by inflammatory mediators is an important step for the progression of inflammation in the skin and possibly also in other autoimmune diseases.
Gesehen am 27.03.2019